Productivity of lettuce Lactuca sativa in high tunnel conditions on Vitric haplustands soil - Velásquez V., Pedro; Ruíz E., Hugo; Chaves J., Germán; Luna C., Cristina (Revista de Ciencias Agrícolas, 2014)
Urban agriculture is an important part of food production for an increasing population. In this context, the aim of this research was to evaluate lettuce Lactuca sativa var. Batavia crop productivity under high tunnel conditions, with three levels of fertilization. The study was conducted at the locality of San Felipe, in the municipality of Pasto, Nariño, in a Vitric Haplustands soil. Two types of environments (high tunnel condition and open field) were evaluated, with three fertilization levels: high 115; 69; 210 kg/ha (N, P2 O5, k2O), and low 46; 11.5; 90 kg/ha (N, P2 O5, k2O), medium 69; 23; 150 kg/ha (N, P2 O5, k2O). The high tunnel was built with bamboo arches and a plastic cover for greenhouses. The trial was established in a split plot design under randomized complete blocks with a divided fringe array. The evaluated agronomic variables were: head weight (HW), dry matter percentage (aerial and root), head diameter (HD), days to harvest (DH), and yield (Y). Additionally, an economic partial budget analysis was performed. The results showed that the lettuce cropunder the hightunnel environment exhibited: HW= 2.24 kg/ plant; HD=20.33 cm, and DH= 74 days.These values showed statistically significant differences compared to the open field. On the other hand, the percentage of aerial dry matter showed no significant differences in any of the treatments. Asimilar situation occurred with high, medium, and low fertilization doses (N, P, K), and with the interactions of these with the two environments tested. The economic analysis showed that the highest profits were obtained in thehigh tunnel environment, with 11278 pesos/m 2 (US$5.13 /m2 ) and a return of 507%.